Practical Implementation of Campus Facility Management Performance Measurement in Qatar - Gunduz, Murat; Naji, Khalid; Maki, Omar (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
Effective facility management is crucial to overall firm performance and is becoming a core competency for organizations seeking to gain a competitive advantage and attain their goals. Recent research on facility management indicates that ineffective management is a leading cause of budget overruns, maintenance delays, reworks, variations, non-compliance events, unnecessary risk, and dissatisfied customers. In Qatar, there is an expansion of educational facilities to achieve the 2030 Qatar National Vision of having an educated population through a well-developed, accountable, and accessible educational system. This expansion is causing a growing demand for effective campus facility management (CFM) in order to effectively manage and accurately monitor the performance of campus facilities. Through a comprehensive literature review, expert interviews, and online questionnaire responses, this paper aims to develop a Campus Facility Management Performance Framework (CFMPF) that consists of tactical and strategic critical campus facility management success factors categorized into process groups. The proposed framework provides an operational foundation for benchmarking the CMF performance to support the identification of underperforming areas. The CFMPF has been used in real-world facility management firms to benchmark their performance and determine which areas of management need to be improved.